A thermoelectric device based on highly elastic and compressible graphene / organic composite foam and its preparation method
Through the composite preparation of graphene, polydimethylsiloxane and NaCl, the rigidity and brittleness problems of traditional flexible thermoelectric materials are solved, and the thermal foam with high elasticity and high thermoelectric properties is achieved, which promotes the development of self-powered wearable electronics.
Patent Information
- Application Number
- CN202111280317.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-01
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-11-01
AI Technical Summary
Traditional flexible thermoelectric materials are difficult to meet the actual power consumption needs of low-power electronic devices, and their stiffness and brittleness reduce the flexibility and comfort of thermoelectric devices, limiting the development of self-powered wearable electronics.
By mixing graphene with polydimethylsiloxane (PDMS) and NaCl, a highly elastic and compressible graphene/organic composite thermoelectric foam was prepared. NaCl was used as a pore-forming agent, and NaCl was removed by heating curing and water-soluble to obtain Thermal foam with a porous structure is connected to silver glue and copper sheet to form high-performance thermoelectric devices.
Thermal foam with high thermoelectric properties, high elasticity and high compression is achieved, the preparation process is simplified, the cost is reduced, and the application prospects are shown in the fields of temperature/strain monitoring and thermoelectric wearables.
Smart Images

Figure CN114005928B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of highly elastic compressible thermoelectric foam and preparation and application thereof, and particularly relates to a preparation method and application of highly elastic compressible graphene / organic composite thermoelectric foam. Background Art
[0002] Based on the Seebeck effect, flexible thermoelectric materials can directly convert thermal energy into electrical energy. Traditional batteries and capacitors as power sources require frequent maintenance and charging, which brings inconvenience to the use of flexible electronic devices. Therefore, the use of flexible thermoelectric materials to directly convert thermal energy into electrical energy and power flexible electronics is of great significance in the field of sustainable green energy and self-powered wearable electronics, and has great application prospects. However, due to the theoretical limitations of thermoelectric conversion efficiency, the traditional flexible thermoelectric materials reported so far are difficult to meet the actual power demand of low-power electronic devices, so the development of self-powered wearable electronics still faces huge challenges. In order to prepare high-performance flexible thermoelectric materials and devices, a common method is to design inorganic thermoelectric materials with high thermoelectric performance into an array structure and combine them with an organic flexible substrate. However, this design scheme often relies on advanced micromachining technology and complex material preparation technology. The preparation process is relatively complex, the cost is high, and the equipment precision is required to be high. In addition, for traditional commercial inorganic thermoelectric materials, such as bismuth telluride-based thermoelectric materials, their stiffness and brittleness reduce the flexibility and comfort of thermoelectric devices. Therefore, the design and application of flexible thermoelectric materials and devices still face huge challenges.
[0003] Graphene and carbon nanotubes are two important carbon nanomaterials. Due to their unique electron transport properties, they are widely used in energy fields such as thermoelectricity and optoelectronics. Through structural design and regulation, the reported carbon nanotube-based thermoelectric fibers and graphene-based thermoelectric films can be used to make flexible and wearable thermoelectric devices. However, these carbon nanomaterials have high thermal conductivity due to their special low-dimensional structure, which leads to poor thermoelectric performance. Taking graphene as an example, although researchers have improved the thermoelectric properties of graphene by designing different structures and chemical treatments, most graphene-based thermoelectric materials are two-dimensional film structures or three-dimensional blocks, and their Seebeck coefficients are mostly less than 40μV / K. Aerogel has a three-dimensional porous structure, and its thermal conductivity can be regulated by porous structure design. Inspired by it, the strategy of three-dimensional structure design and regulation is applied to the design and optimization of flexible thermoelectric materials, which is expected to obtain excellent thermoelectric performance and promote the development of self-powered wearable design. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a highly elastic and compressible graphene / organic composite thermoelectric foam, and at the same time provide a preparation method and application of the thermoelectric foam, and achieve high thermoelectric performance, high elasticity and high compressibility of the graphene foam through structural design and regulation.
[0005] The present invention provides a method for preparing a highly elastic and compressible graphene / organic composite thermoelectric foam, wherein the thermoelectric foam is a composite porous foam of graphene and polydimethylsiloxane (PDMS). The thermoelectric foam is obtained by heating and curing a mixture of graphene, PDMS and NaCl and removing NaCl by water dissolution.
[0006] The invention discloses a highly elastic and compressible graphene / organic composite thermoelectric foam and device, and the preparation method thereof comprises:
[0007] (1) Mix graphene, NaCl and PDMS in a certain proportion and stir them thoroughly until they are uniform;
[0008] (2) filling the uniform mixture in step (1) into a mold, pressing it tightly, placing it in an oven for heating and curing, and then taking it out to cool;
[0009] (3) taking out the graphene composite block cooled in step (2) from the mold, soaking it in hot water until the NaCl is completely dissolved, and then taking out the foam and drying it in an oven to obtain a highly elastic and compressible graphene / organic composite thermoelectric foam;
[0010] (4) Silver glue is coated on the upper and lower surfaces of the thermoelectric foam and connected to a copper sheet. After drying again, a highly elastic and compressible graphene foam thermoelectric device is obtained.
[0011] The relative contents of graphene and PDMS in step (1) are 60, 70, 80, 90, 100, 110, and 120 mg of graphene per 1 g of PDMS, respectively; the mass ratio of PDMS to NaCl is 1:5 to 1:15; and the average particle size of NaCl is 150 to 800 μm. The temperature in step (2) is 60 to 120° C., and the heating time is 1 to 5 hours. The hot water temperature in step (3) is 30 to 100° C., and the soaking time is 5 to 48 hours.
[0012] The invention provides a highly elastic and compressible graphene / organic composite thermoelectric foam prepared by the method. The thermoelectric foam is made of graphene and PDMS as raw materials, and NaCl is used as a pore-forming agent, and can be obtained by simple heating, dissolving and drying.
[0013] The present invention provides an application of the highly elastic and compressible graphene / organic composite thermoelectric foam, such as temperature monitoring, strain monitoring, and thermoelectric wearable fields.
[0014] The beneficial effects are:
[0015] (1) The preparation method of the present invention is simple and easy to implement, and has the potential for mass production;
[0016] (2) The highly elastic and compressible graphene / organic composite thermoelectric foam of the present invention has good thermoelectric and mechanical properties;
[0017] (3) The flexible thermoelectric device based on highly elastic and compressible graphene / organic composite thermoelectric foam of the present invention has good application prospects in the fields of temperature / strain monitoring and thermoelectric wearables. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic diagram of the production process for preparing graphene composite thermoelectric foam;
[0019] Figure 2 The composite thermoelectric foam prepared in Example 1, wherein Figure a is a schematic diagram of the porous structure, and Figure b is a SEM photo of the thermoelectric foam;
[0020] Figure 3 This is an optical picture of the graphene thermoelectric foam prepared in Example 1, indicating that the thermoelectric foam has the characteristics of light weight and high strength. Figure a shows the thermoelectric foam supported by asparagus fern leaves, and Figure b shows the prepared thermoelectric foam supporting a 180g aluminum block;
[0021] Figure 4 The Seebeck coefficient and conductivity images of graphene thermoelectric foams with different porosities prepared in Example 1;
[0022] Figure 5 The Seebeck coefficient and conductivity images of thermoelectric foams with different graphene mass fractions prepared in Example 1 and Example 2;
[0023] Figure 6 The Seebeck coefficient and conductivity images of graphene thermoelectric foams with different pore sizes prepared in Example 3;
[0024] Figure 7 This is a stress-strain cycle curve image of the graphene thermoelectric foam prepared in Example 3 under a strain of 30%;
[0025] Figure 8 The practical application of the graphene thermoelectric foam prepared in Example 3, FIG. a is a micro temperature monitoring application, and FIG. b is a micro strain monitoring application;
[0026] Fig. 9 Pictures of micro-temperature monitoring and micro-strain monitoring for thermoelectric foam;
[0027] Fig.10 The graphene thermoelectric foam array prepared in Example 3 is integrated into the insole for body temperature power generation. Figure a is a photo of the thermoelectric foam array integrated into the insole, Figure b is a schematic diagram of body temperature power generation shoes based on thermoelectric foam, and Figures c and d are pictures of the voltage output of the thermoelectric device when stepping on a cold source and a heat source, respectively. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0029] Highly conductive few-layer graphene powder (size 20-80 μm) was purchased from Deyang Encarbon Technology Co., Ltd., polydimethylsiloxane (PDMS, Sylgard 184) was produced by Dow Corning, USA, and sodium chloride (NaCl) was provided by Shanghai Aladdin Co., Ltd.
[0030] The test method involved in the embodiment: the Seebeck coefficient of the thermoelectric foam is tested using a self-built test device. A low-voltage power supply and a commercial Peltier heating module are used to control the temperature at the bottom of the sample and the temperature difference between the upper and lower ends. The open circuit voltage at both ends of the thermoelectric foam is measured using a Keithley 2450 data acquisition system. At the same time, an infrared imager is used to measure the real-time temperature at the upper and lower ends of the foam to obtain the temperature difference and calculate the Seebeck coefficient. The thermoelectric foam designed in the embodiment of the present invention takes a cylindrical structure as an example, with a height and diameter of 16 mm. The upper and lower ends are connected to copper sheets as electrodes through silver paste. Keithley 2450 is used to measure the resistance at the upper and lower ends of the thermoelectric foam. According to the length, resistance, and cross-sectional area of the thermoelectric foam, its resistivity is calculated and converted into conductivity. The compression strain test of the thermoelectric foam is implemented by a universal testing machine test system, and is connected to the Keithley 2450 system to record all electrical signals in real time.
[0031] Embodiment 1:
[0032] See attached Figure 1 Flow chart, the preparation method of the composite thermoelectric foam of the present invention is:
[0033] (1) 80 mg of graphene powder, 1.0 g of PDMS and 9 g of NaCl (average size of 250 μm) were mixed thoroughly, and then the required amount was poured into a cylindrical mold, pressed tightly, and then placed in an oven at 80 ° C for heating and curing for 1 h, and then taken out and cooled;
[0034] (2) taking the cooled graphene composite block out of the mold, soaking it in 80° C. hot water for 10 h to completely dissolve the NaCl, and then taking out the composite foam and placing it in an oven at 80° C. for drying to obtain a highly elastic and compressible graphene / organic composite thermoelectric foam;
[0035] (3) Silver glue is coated on the upper and lower surfaces of the thermoelectric foam and connected to a copper sheet. After drying again, a highly elastic and compressible graphene foam thermoelectric device is obtained.
[0036] Attached Figure 2 The thermoelectric foam prepared by the present invention is composed of the following Figure 2 The structural diagram of a shows that the thermoelectric foam has a porous structure. Figure 2 b It can be seen that the average pore size of the thermoelectric foam is about 250 μm, which is consistent with the size of the NaCl used.
[0037] Attached Figure 3 This is an optical picture of the thermoelectric foam prepared by the present invention, Figure 3 a It can be seen that graphene foam can be carried by asparagus fern leaves, indicating that its density is relatively small. Figure 3 b It can be seen that although the thermoelectric foam is light and has a low density, it has great mechanical strength and can support a 180g aluminum block.
[0038] Through testing and calculation, it can be obtained that the porosity of the graphene thermoelectric foam prepared by the present invention is 69.8%, and the average Seebeck coefficient and conductivity are 45.0 μV·K -1 and 7.5S·m -1 , see attached Figure 4 .
[0039] Comparative Example 1:
[0040] According to Example 1, the relative content of NaCl in step (1) was changed to 5g, 7g, 11g, 13g, and 15g respectively, and the rest was the same as Example 1. Calculation showed that the porosity of the five foams in the comparative example was 64.6%, 67.8%, 71.1%, 72.0%, and 72.7% respectively. Figure 4 The Seebeck coefficients and electrical conductivities of six thermoelectric foams, including the thermoelectric foam in Example 1, are given. As the porosity of the thermoelectric foam increases, the electrical conductivity gradually decreases from 8.7 to 3.0 S·m -1 , the Seebeck coefficient gradually increases from 43.5μV·K -1 Increased to 49.5μV·K -1 .
[0041] Embodiment 2:
[0042] See attached Figure 1 Flow chart, the preparation method of the composite thermoelectric foam in this embodiment is:
[0043] (1) 80 mg of graphene powder, 1.0 g of PDMS and 9 g of NaCl (average size of 250 μm) were fully mixed, and the remaining steps were the same as in Example 1 to prepare graphene thermoelectric foam.
[0044] (2) The relative contents of graphene in the above proportions were changed to 60 mg, 70 mg, 90 mg, 100 mg, 110 mg, and 120 mg, respectively, and mixed with 1.0 g of PDMS and 9 g of NaCl (average size of 250 μm), respectively. The remaining steps were the same as in Example 1, and another 6 groups of graphene thermoelectric foams were obtained.
[0045] Through test calculation, the contents of graphene in the seven groups of thermoelectric foams in this embodiment are 5.66%, 6.54%, 7.41%, 8.26%, 9.09%, 9.91%, and 10.71%, respectively. Figure 5 The Seebeck coefficients and electrical conductivity of these seven groups of thermoelectric foams are given. It can be seen that with the increase of graphene content, the electrical conductivity of the thermoelectric foam increases from 2.5S·m -1 Gradually increased to 9.6S·m -1 , the Seebeck coefficient is from 49.2μV·K -1 Reduced to 45.9μV·K -1 .
[0046] Embodiment 3:
[0047] Through the optimization comparison of Example 1 and Example 2, 90 mg of graphene powder, 1.0 g of PDMS and 9 g of NaCl were selected as fixed proportions, the graphene content was 8.26% and the porosity was 69.8%. NaCl with different particle sizes was selected as the pore-forming agent. In this embodiment, 5 kinds of NaCl particles were selected, and the average sizes were 150 μm, 250 μm, 350 μm, 500 μm and 800 μm, respectively. See also the attached Figure 1 The preparation schematic diagram is shown in FIG. , and the remaining steps are the same as those in Example 1 and Example 2.
[0048] Attached Figure 6 The Seebeck coefficient and conductivity of the five groups of thermoelectric foams with different pore sizes are given. It can be seen that with the increase of the average particle size of NaCl, the conductivity and Seebeck coefficient of the thermoelectric foam first increase and then decrease. The thermoelectric foam with an average pore size of 500 μm has the best performance, with a conductivity of 8.5 S·m -1 , the Seebeck coefficient is 47.2μV·K -1 .
[0049] In addition, Figure 7 The 30% compression strain cycle curve of the thermoelectric foam for 3000 cycles is given, and it can be seen that the thermoelectric foam has excellent mechanical cycle stability. Figure 8 a shows the relative changes in voltage (corresponding to a temperature difference of 16K) and resistance during 3000 cycles of 30% compressive strain. Figure 8b shows the current change of the thermoelectric foam under 0% and 30% compressive strain states when the temperature difference is 16K. It can be seen that the thermoelectric foam has excellent electrical stability.
[0050] In order to verify the practicality of the thermoelectric foam in the invention, the optimized thermoelectric foam was selected for temperature monitoring and strain monitoring, as shown in the attached figure. Fig. 9 As shown in a, the thermoelectric foam can monitor small temperature changes of 0.1 K. By applying a constant temperature difference (16 K) to the thermoelectric foam, small strain monitoring of 0.3% can be achieved.
[0051] Finally, multiple thermoelectric foams (1 cm in diameter and 2 cm in height) were integrated in series into the sole, as shown in the attached Fig.10 As shown, it is expected that a smart shoe that uses human body heat to generate electricity can be designed. The soles of the shoes with integrated thermoelectric devices are placed on a cold source (0℃) and a heat source (70℃), which simulates the ground temperature in winter and summer respectively. At the same time, by stepping on them, the temperature difference between the human body and the ground can be used to achieve thermoelectric power generation. When stepping on the cold source and the heat source, a stable voltage of 70mV and 90mV can be generated respectively.
[0052] It should be further explained that in the raw materials of the present invention: graphene is replaced by other inorganic or organic thermoelectric materials, including but not limited to carbon nanotubes, carbon fibers, fullerenes, and a carbon material in graphene, or traditional bismuth telluride-based thermoelectric materials, or a two-dimensional material in new MXene, WS2, and MoS2; PDMS is replaced by but not limited to a polymer material in commonly used PVA, PU, PVDF, NBR, Ecoflex, and Rcoflex; the pore-forming agent NaCl is replaced by but not limited to a salt particle in K2SO4, KCl, and Na2SO4, or one of sugar cubes and white sugar. The products obtained by the preparation method of the present invention using each of the alternative materials achieve the same technical effects as the embodiments of the present invention.
Claims
1. A thermoelectric device based on highly elastic and compressible graphene / organic composite foam, characterized in that: The thermoelectric device is obtained by connecting copper sheets as upper and lower electrodes on the upper and lower surfaces of thermoelectric foam respectively through conductive silver glue, and the preparation method is as follows: 1) mixing graphene, sodium chloride NaCl, and polydimethylsiloxane PDMS, and fully stirring until uniform; 2) filling the uniform mixture in step 1) into a mold, pressing it tightly, putting it in an oven for heating and curing, and then taking it out and cooling it; 3) taking out the graphene composite block in step 2) from the mold, soaking it in hot water until NaCl is completely dissolved, then taking out the foam, putting it in an oven for drying, and obtaining the thermoelectric foam; 4) coating the upper and lower surfaces of the thermoelectric foam with silver glue, connecting them with the copper sheet, and drying them again, so as to obtain a highly elastic and compressible graphene foam thermoelectric device; The mass ratio of PDMS to NaCl in step 1) is 1:5 to 1:15, and thermoelectric foams with different porosities are obtained by changing the NaCl content, thereby achieving regulation of thermal conductivity; the mass ratio of graphene to PDMS is 1:20 to 1:5, and the conductivity and thermoelectric properties of the thermoelectric foam are regulated by changing the graphene content; The average particle size of the NaCl used is 150-800 μm, and thermoelectric foams with different pore sizes are obtained by changing the particle size of the NaCl used.
2. A thermoelectric device based on highly elastic and compressible graphene / organic composite foam according to claim 1, characterized in that: The preparation method of the thermoelectric foam is as follows: graphene, NaCl and PDMS are uniformly mixed, filled into a mold and pressed tightly, and then placed in an oven for heating and curing, wherein the temperature range is 60 to 120° C. and the heating time is 1 to 5 hours; the soaking hot water temperature is 30 to 100° C. and the soaking time is 5 to 48 hours until the NaCl is completely dissolved, and the thermoelectric foam is a porous cylinder or cube.
3. The thermoelectric device based on highly elastic and compressible graphene / organic composite foam according to claim 1 or 2, characterized in that: 1) Graphene is replaced by a carbon material selected from carbon nanotubes, carbon fibers, fullerenes, and graphyne, or a traditional bismuth telluride-based thermoelectric material, or a two-dimensional material selected from WS2 and MoS2; 2) PDMS is replaced by a polymer material selected from PVA, PU, PVDF, NBR, Ecoflex, and Rcoflex; 3) The pore-forming agent NaCl is replaced by a salt particle selected from K2SO4, KCl, and Na2SO4, or a sugar cube or white sugar.
4. The method for preparing a thermoelectric device based on highly elastic and compressible graphene / organic composite foam according to any one of claims 1 to 3, characterized in that: It is prepared by highly elastic and compressible graphene thermoelectric foam.
5. Application of the thermoelectric device based on highly elastic and compressible graphene / organic composite foam as described in any one of claims 1 to 3 in sensing monitoring, photothermal evaporation, seawater desalination, thermal insulation or wearable electronics.
Citation Information
Patent Citations
Thermoelectrically active aerogel
DE102013112522A1
Sensitive, high-strain, high-rate, bodily motion sensors based on conductive nano-material-rubber composites
US20160287175A1